Language Diversity in Japan - Wedayanti, NPL (e-Journal of Linguistics, 2024)
As the world becomes more borderless, it is hard to find any country that remains homogeneous. Japan, which is well-known as a homogeneous and monolingual country, also has diversity in their language phenomenon. This study uses a qualitative research approach, because the direction of this research is to examine language phenomena that occur in Japanese society as the subject and source of this research. Even within Japanese people there is sign language that is used by the Japanese Deaf or hearing people who sign fluently. The Japanese sign language ( nihon shuwa ) has its own system different from the Japanese language. The presence and increasing recognition of sign language has created awareness of heterogeneity and diversity in culture in Japan.